"THE REALITY OF THE STRATEGIC ENVIRONMENTAL ANALYSIS (SWOT) FOR THE QUALITY OF ADMINISTRATIVE PERFORMANCE OF DEANS OF COLLEGES OF PHYSICAL EDUCATION AND SPORTS SCIENCE IN BAGHDAD, FROM THE PERSPECTIVE OF ITS MEMBERS" (American Journal of Pedagogical and Educational Research, 2023)
The aim of the research is to identify the reality of the administrative performance of deans of colleges of physical education and sports science from the perspective of the faculty members. The research community consisted of faculty members in colleges of physical education and sports science at the University of Baghdad, the University of Mustansiriya, and the colleges of physical education and sports science in Al-Jadriya, Al-Mustansiriya, and Al-Waziriya. The research community consisted of 314 faculty members, and the researchers used a descriptive survey method because it suits the nature of the problem-solving.